(untitled) (Global Journal of Human-Social Science, 2012)
Throughout many years physical manifesta-tion phenotype and inheritable information genotype are researched with different scientific methodologies in medicine genetics biology physiology psychology etc The dependence of physical traits on genetic code of individual can be established through various intensive mathematical models This article explores one of the models that hypothetically explains segregation of people based on their observable psychological traits Although environment can influence behavioral traits the predisposition towards them controlled by fundamental genes and thus might be inherited The proposed mathematical model consumm-ates that the process of human segregation leads to a break down on non-active and active communities As a result more active community has a tendency to develop much faster and dominate over non-active community This result of this hypothesis can help to determine and eliminate various risks of denomination and develop scientifically proven recommendations to improve immigration politic